INCREASING STEPS OF MUSIC IN INDIA: भारत में संगीत के बढ़ते हुए कदम - Kumar Ojha, Narendra (International Journal of Research -GRANTHAALAYAH, 2015)
India’s civilization and culture is historical. There is no music knowledge in India today, it is very old. Even today many high-ranking artists have made their place in history such as Bhaskar Buwa, Mian Jan, Abdul Karim Khan, Fayaz Kha, Hyder Kha, Wazir Kha, Hafeez Kha, Omkarnath Thakur etc. The central and state governments have contributed significantly to the development of Indian art, with the central government giving scholarships to eligible students. Students are thus encouraged. भारत की सभ्यता और संस्कृति ऐतिहासिक है। भारत में संगीत विषयक ज्ञान कोई आज का नहीं है, यह बहुत पुराना है। इतिहास में आज भी कई उच्च श्रेणी के कलाकार अपना स्थान बना चुके है जैसे- भास्कर बुवा, मियाॅं जान, अब्दुल करीम खाॅ, फैयाज खाॅ, हैदर खाॅ, वजीर खाॅ, हफीज खाॅ, ओंकारनाथ ठाकुर आदि। भारतीय कला के विकास में केन्द्र और राज्य सरकारों का महत्वपूर्ण योगदान रहा है, केन्द्रीय सरकार षिक्षा पात्र विद्यार्थियों को छात्रवृत्ति दे रही है। इस प्रकार से विद्यार्थियों को प्रोत्साहन मिल रहा है।